Guarantees for the Implementation of Administrative Judiciary Rulings in the Face of the Administration - Omar Mahdi Hamdi; Ragab Muhammed Nada (Journal of Legal Sciences, 2024)
Guarantees for the execution of judicial judgments are represented in cases where administrative authorities refuse to execute the judgments of administrative courts, explicit or incomplete refusal of the judgment, fraud or non-accurate execution of the judgment, and obstructing the execution of the judgment by individual administrative decisions or legislation issued. The main problem is that the guarantees for the execution of judicial decisions issued by the Egyptian administrative courts are insufficient, as the existing traditional guarantees are still insufficient; in addition, the extent of commitment of the administrative authorities to implement the decisions is insufficient. The main purpose of the study is to demonstrate the guarantees for the implementation of administrative sentences, by showing the extent of its impact on the failure to achieve the purpose required for issuing a judicial sentence, as well as the need to urge the Egyptian legislator to adopt the modern guarantees of issuing judicial orders to the executive authority and the threat of fines used in French law. The study was divided into two sections, in the first section we discussed the cases in which the administration refrains from implementing the judgments of the administrative courts, by clarifying the cases in which the administration refrains from implementing the judgments of the administrative courts in the first request, then the extent of the administrative judge’s authority to issue orders to the public administration as a second request, and in the second section we discussed the means of forcing the administration to implement the implementation of the administrative court judgments as a guarantee for the litigant in both France and Egypt in two requests. This study found that the threatening fine is a legitimate means of coercion or coercion against the debtor in order to fulfill his obligation, as well as that the French legislator has violated the Egyptian legal system on the non-criminalization of refraining from executing judicial sentences